2015
DOI: 10.7439/ijasr.v1i6.2189
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Serum Minerals and Electrolytes In Thyroid Patients

Abstract: Introduction: The effect on thyroid hormones on electrolytes and minerals has not been well established and the underlying mechanisms are not well understood. Only few data on the association between thyroid function and electrolyte disorders exists. Thus our aim was to assess the levels of serum electrolytes and minerals in the patients with thyroid disorders. Materials and methods: 75 patients and 30 controls were included. Thyroid hormones (T3, T4, TSH) were measured by vidas autoanalyser. Serum calcium, ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…not well established. Bharti et al 6 in his study done on subclinical hyperthyroid patients show that there were no significant changes in the levels of serum sodium, potassium, and chloride which is similar to my study. Along with this in our study, the correlation between the levels of serum sodium, potassium, and chloride with TSH showed little negativity or no changes in SHE.…”
Section: Discussionsupporting
confidence: 89%
“…not well established. Bharti et al 6 in his study done on subclinical hyperthyroid patients show that there were no significant changes in the levels of serum sodium, potassium, and chloride which is similar to my study. Along with this in our study, the correlation between the levels of serum sodium, potassium, and chloride with TSH showed little negativity or no changes in SHE.…”
Section: Discussionsupporting
confidence: 89%
“…Which has similarity with some other studies. [16][17][18] There is significant positive relation of calcium with T3 and T4. Significant negative relation was found in calcium with TSH in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have shown a decrease in serum magnesium in hypothyroidism whereas S Porta et al have shown a significant decrease in total serum magnesium in hyperthyroid patients. According to Shrestha S et al 31 both plasma magnesium and ionized magnesium were increased in hypothyroidism when compared to controls. In hypothyroidism, filtered magnesium is reabsorbed more as the thyroid hormone has a direct effect on renal tubules resulting in renal retention of magnesium if thyroid hormones are chronically absent.…”
Section: Et Al Mortoglou a Et Almentioning
confidence: 96%